Impact of oral health on the quality of life of Paraguayan adults - Clarisse Díaz-Reissner; Juan Roldán-Merino; Irma Casas García (Journal of Oral Research, 2021)
Introduction: Alterations in the oral cavity can affect people’s quality of life, hence it is important to determine how the individual perceives their own health. Objective: To determine the oral health-related quality of life in adults who received dental care at establishments managed by the Ministry of Public Health and Social Welfare of Paraguay, the School of Dentistry of Universidad Nacional de Asunción, and the “Chacarita” Community Center, in Paraguay, in the first quarter of 2017. Material and Methods: A cross-sectional study was carried out. The Paraguayan version of the Oral Health Impact Profile (OHIP-14Py) was used. Spearman's correlation, Kruskal-Wallis, and Mann-Whitney tests were used to relate the impact of oral health with demographic, labor, educational, and clinical variables. Results: 333 subjects participated in the study. The most affected domains were physical pain, psychological distress, and psychological disability. The correlation between OHIP-14Py and DMF-T was positive but poor (r=0.236; p=<0.001). The oral health-related quality of life was significantly lower in subjects with abnormal oral mucosa (p=0.020), presence of TMJ symptoms (p=0.026), need for prostheses (p<0.001), higher level of severity of DMF-T (p<0.001), use of upper (p=0.004) and lower (p<0.001) prostheses, and absence of functional dentition (p<0.001). Conclusion: Primary and secondary preventive measures should be promoted since oral health status can negatively influence people’s quality of life and may even cause total inability to carry out daily activities.